THE PECULIARITIES OF TEACHING ENGLISH FOR SPECIFIC PURPOSES(ESP) - Xamzayev, Sobirr (Журнал иностранных языков и лингвистики, 2021)
The aspects that are to be considered when teaching English specific purposes are discussed in the article. The author also discusses brief history of developing ESP as a special methodology of teaching the English language.